Forms of expressing anger in hospitalised Ukrainian post-deployed™ service members - Ortenburger, Dorota; Wąsik, Jacek; Tsos, Аnatolіi; Bielikowa, Natalia; Andrijchuk, Olga; Indykа, Svitlana (My University, 2018)
Introduction. Military actions and injuries sustained make returning to ordinary life and everyday routine a challenge which soldiers need to face. Research on this subject shows that the consequences of post-traumatic stress extends further, beyond the victim’s everyday life, resulting in health problems and problems with social relationships. Objective. The aim was to gather knowledge of the ways of expressing anger in a group of hospitalized Ukrainian postdeployed servicemen. A research study was conducted concentrating on the two forms of managing anger, i.e. releasing or suppressing anger, and posing the following question: ‘How are they manifested in the hospitalized Ukrainian combat veterans? Materials and method. The study included 35 hospitalized soldiers who had taken part in military operations in Ukraine (age: 34.61±9.23; age range: 21–56 years of age). The research was conducted in the hospitals in Lutsk. Measurements were conducted with the use of certified psychological tests, i.e. Anger Expression Scale (AES), medical documentation and oral reports given by the persons conducting the study. Results. The average value of the suppressed anger indicator was 31.57±6.23 (p<0.05); respective value of the released anger 24.37 ±6.34 (p<0.05). For released anger, results at the level of the upper quartile (Q3=28) and above were obtained by 28.57 % of the soldiers in the study, while in the case of repressed anger, the results obtained at the level of the upper quartile (Q3 = 36) and above that value were obtained by 34.27% of the soldiers/patients. Conclusions. The results obtained show that in the group of hospitalized patients/soldiers there is a higher level of repressed anger intensity than in the case of released anger. The study survey suggests that in their case expressing anger is usually a reaction to somebody’s inappropriate-in-their-eyes behaviour. Curbing anger takes on various forms, from trying not to express annoyance and/or rage, to trying to keep calm in spite of growing anger caused by other people’s behaviours.
Keywords: anger; anger expression; repressed; anger; injury; soldiers